Recent advances in the construction of biocomposites based on fungal mycelia - Li, Ke; Jia, Jianyao; Wu, Na; Xu, Qing (Frontiers in Bioengineering and Biotechnology, 2022)
In recent years, environmental problems have become increasingly serious, significantly effecting the ecosystem and human health. To deal with the problem of environmental pollution in an eco-conscious way, sustainable composite biomaterials are being produced. Mycelium-based composite biomaterials combine biological systems with substrates such as nanomaterials or agricultural and industrial wastes, which can complement each other's advantages or turn waste into a useful resource. Such materials can solve practical wastewater problems as well as replace plastic products, thus reducing plastic pollution and contributing to the green transition of the environment. In this review, we summarized the recent findings of studies on these materials, indicating future research directions.